All‐Graphene Core‐Sheath Microfibers for All‐Solid‐State, Stretchable Fibriform Supercapacitors and Wearable Electronic Textiles. (6th March 2013) - Meng, Yuning; Zhao, Yang; Hu, Chuangang; Cheng, Huhu; Hu, Yue; Zhang, Zhipan; Shi, Gaoquan; Qu, Liangti
<x xml:space="preserve">Abstract</x> Unique all‐graphene core–sheath fibers composed of a graphene fiber core with a sheath of 3D graphene network have been developed. Used as flexible electrodes, all‐solid‐state fiber supercapacitors have been fabricated, which can be managed to highly compressible and stretchable spring supercapacitors and can also be woven into a textile for wearable electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>